Advanced Intermittent Auscultation (AIA)’ of Fetal Heart Rate in Labour – Launch of a Scientific, Reliable and Forward-Looking Training Module for Birth-Attendants, Combining Simplicity with Sound Bayesian Foundation and Modern Technology - Sholapurkar, S. L.; Capper, Tanya (British Journal of Healthcare and Medical Research, 2024)
Intrapartum fetal heart rate (FHR) monitoring has very wide clinical application of vital importance. However, there are several different methods of Intermittent auscultation (IA) which continue to suffer from some shortcomings and even inaccuracies resulting in birth asphyxia. Clinical studies alone have not provided the epistemic perfection for IA or cardiotocography (CTG). However, integrating them with the understanding of fetal pathophysiology, practical experience and critical thinking during adverse event investigations provides functional knowledge required for reliable and efficient IA. The “Advanced Intermittent Auscultation (AIA)” regime and training module published in 2022, pragmatically uses the current knowledge-base retaining simplicity of IA while maximising the benefits of widely available affordable modern but simple technology, thus improving efficiency, reliability and accuracy of IA. In addition, AIA opens the possibility judging the FHR baseline variability in future, unfeasible with previous regimes. Many current IA regimes, by mistakenly insisting on actually counting the fetal heart tones, have failed to make progress and remain unsafe, and hence best abandoned. This article describes in detail the foundational concepts of “Advanced Intermittent Auscultation (AIA)”. It demonstrates the superiority of handheld Doppler monitors which should be preferentially used. Importantly, ‘auscultation’ should not mandate ‘actual counting’ by single or multiple-count methods, which is laborious and less accurate. The FHR displayed on the Doppler device has the same accuracy as that on the CTG. Simply observing this display (and modest attention to the tempo of heart sounds) constitutes the most reliable technique of inferring FHR periodic variations. The FHR display should be observed from the latter part of contraction to the beginning of the next contraction (or eventually a full contraction-relaxation cycle). AIA maintains the benefits of the simplicity of IA by avoiding unwarranted, impractical and unproven addition of parameters like FHR cycling or post-deceleration overshoots. The AIA regime is comprehensive, pragmatic, practical, non-laborious (facilitating more holistic care), more accurate / reliable and thus enhances patient safety. Hence, AIA should be adopted worldwide including by the national professional bodies in UK, Europe, Americas and Australasia.